Biphasic (HA/β-TCP) calcium phosphate ceramics - Zyman, Z.Z.; Tkachenko, N.V.; Polevodin, D.V. (Functional Materials, 2007)
A new manufacturing technique for dense and porous biphasic calcium phosphate (BCP) ceramics of hydroxyapatite HA/I3-tricalcium phosphate (β-TCP) composition has been proposed. The idea consisted in the combination of precipitation and solid phase methods. The HA/β-TCP ratio in the ceramics on the preparation conditions has been established. The ceramics phase composition was formed within 600-1000°C range and was stable up to 1200°C. The DCP ceramics microhardness was independent of its composition. However, for the compressive strength, the following correlation has been found: the smaller is the HA/β-TCP ratio, the higher the strength is. The correlation is associated with a hardening that could be due to the disperse state of β-TCP particles formed in the ceramics during sintering.